Chronological and paleoceanographic constraints of Miocene to Pliocene 'mud sea' in the Ryukyu Islands (southwestern Japan) based on calcareous nannofossil assemblages. (21st October 2013) - Imai, Ryo; Sato, Tokiyuki; Iryu, Yasufumi
Abstract: The Cenozoic sedimentary succession in Okinawa‐jima, including the upper Miocene to Pleistocene siliciclastic deposits (Shimajiri Group) and the Pleistocene reef to shelf deposits (Ryukyu Group), suggests a drastic paleoceanographic change from a 'mud sea' to a 'coral sea.' To delineate the paleoceanographic evolution of the mud sea, we quantified the stratigraphic distribution of the calcareous nannofossil assemblages from the Shimajiri Group in a 2119.49 m‐deep well (Nanjo R1 Exploratory Well) drilled in southern Okinawa‐jima (Ryukyu Islands, southwestern Japan). Four late Miocene and Pliocene datum planes were found in the studied interval: the first occurrence of Amaurolithus spp. (7.42 Ma), the last occurrence of Discoaster quinqueramus (5.59 Ma), the first occurrence of Ceratolithus rugosus (5.12 Ma), and the last occurrence of Reticulofenestra pseudoumbilicus (3.70 Ma). The calcareous nannofossil assemblages from the Tomigusuku Formation and the lower part of the Yonabaru Formation are characterized by a lower total number of coccoliths and abundant Sphenolithus abies that is associated, at times, with common Discoaster spp. Overall, these suggest the existence of oligotrophic conditions between 5.3 and >8.3 Ma. The total number of coccoliths increased and small Reticulofenestra spp. became more common in the middle part of the Yonabaru Formation, suggesting that eutrophic conditions were present between 3.5 and 5.3 Ma. The rare occurrence of calcareous nannofossils in the upper part of the Yonabaru Formation indicates a return to oligotrophic conditions at 3.5 Ma. Micropaleontological evidence suggests that these oceanographic changes were likely caused by local tectonic movement (shallowing of the sedimentary basin in which the Shimajiri Group was deposited).